# cos(4x)-cos(2x)=sin(3x)

## Simple and best practice solution for cos(4x)-cos(2x)=sin(3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for cos(4x)-cos(2x)=sin(3x) equation:

Simplifying
cos(4x) + -1cos(2x) = sin(3x)
Remove parenthesis around (4x)
cos * 4x + -1cos(2x) = sin(3x)
Reorder the terms for easier multiplication:
4cos * x + -1cos(2x) = sin(3x)
Multiply cos * x
4cosx + -1cos(2x) = sin(3x)
Remove parenthesis around (2x)
4cosx + -1cos * 2x = sin(3x)
Reorder the terms for easier multiplication:
4cosx + -1 * 2cos * x = sin(3x)
Multiply -1 * 2
4cosx + -2cos * x = sin(3x)
Multiply cos * x
4cosx + -2cosx = sin(3x)
Combine like terms: 4cosx + -2cosx = 2cosx
2cosx = sin(3x)
Remove parenthesis around (3x)
2cosx = ins * 3x
Reorder the terms for easier multiplication:
2cosx = 3ins * x
Multiply ins * x
2cosx = 3insx
Solving
2cosx = 3insx
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Divide each side by '2osx'.
c = 1.5ino-1
Simplifying
c = 1.5ino-1